Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1002/cne.23222
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the hypothalamus of Xenopus laevis during development. I. The alar regions

Abstract: The patterns of expression of a set of conserved developmental regulatory transcription factors and neuronal markers were analyzed in the alar hypothalamus of Xenopus laevis throughout development. Combined immunohistochemical and in situ hybridization techniques were used for the identification of subdivisions and their boundaries. The alar hypothalamus was located rostral to the diencephalon in the secondary prosencephalon and represents the rostral continuation of the alar territories of the diencephalon an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
99
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 64 publications
(122 citation statements)
references
References 174 publications
(431 reference statements)
23
99
0
Order By: Relevance
“…For example xUlk4 expression is found in the PO, which is involved in the control of reproductive behavior and reproduction both in amniotes and anamniotes (Kelley and Pfaff, 1976;Hodos, 1996, 2005;Boulant, 1998;Will et al, 2014;Yaeger et al, 2014). In addition there is high xUlk4 expression detected in the Xenopus hypothalamic territory, which presents a homologous regionalization pattern to the one described in mammals, as has been recently reported by an exhaustive study based on morphogenetic, neurochemical and hodological patterns (AH: supraoptoparaventricular and SCs; BH: tuberal and mammillary regions; Domı´nguez et al, 2013Domı´nguez et al, , 2014. We have observed xUlk4 expressing cells in the supraoptoparaventricular and SCs, which are closely related to the neuroendocrine system, containing neuroendocrine cells involved in the control and regulation of different physiological functions such as social and reproductive behavior, stress response and sleep among others (for a review see Markakis, 2002;Miller and Takahashi, 2013).…”
Section: Xulk4 Expression Patterns In the Forebrainmentioning
confidence: 51%
See 2 more Smart Citations
“…For example xUlk4 expression is found in the PO, which is involved in the control of reproductive behavior and reproduction both in amniotes and anamniotes (Kelley and Pfaff, 1976;Hodos, 1996, 2005;Boulant, 1998;Will et al, 2014;Yaeger et al, 2014). In addition there is high xUlk4 expression detected in the Xenopus hypothalamic territory, which presents a homologous regionalization pattern to the one described in mammals, as has been recently reported by an exhaustive study based on morphogenetic, neurochemical and hodological patterns (AH: supraoptoparaventricular and SCs; BH: tuberal and mammillary regions; Domı´nguez et al, 2013Domı´nguez et al, , 2014. We have observed xUlk4 expressing cells in the supraoptoparaventricular and SCs, which are closely related to the neuroendocrine system, containing neuroendocrine cells involved in the control and regulation of different physiological functions such as social and reproductive behavior, stress response and sleep among others (for a review see Markakis, 2002;Miller and Takahashi, 2013).…”
Section: Xulk4 Expression Patterns In the Forebrainmentioning
confidence: 51%
“…To this aim, we have here studied the expression of Ulk4 during the development of the nervous system in the amphibian Xenopus laevis. In the last years, numerous comparative studies of diverse transcription factor expression patterns in the embryonic brain have strongly supported the idea of a common brain organization pattern across tetrapods (Figdor and Stern, 1993;Rubenstein, 1993, 2003;Pombal and Puelles, 1999;Wullimann and Puelles, 1999;Hauptmann and Gerster, 2000;Puelles et al, 2000;Bachy et al, 2001Bachy et al, , 2002Gonza´lez et al, 2002a,b;Brox et al, 2003Brox et al, , 2004Osorio et al, 2005Osorio et al, , 2006Flames et al, 2007;Abella´n and Medina, 2009;Gonza´lez and Northcutt, 2009;Abella´n et al, 2010;Domı´nguez et al, 2010Domı´nguez et al, , 2011Domı´nguez et al, , 2013Domı´nguez et al, , 2014Moreno et al, 2010Moreno et al, , 2012Moreno and Gonza´lez, 2011;Lo´pez et al, 2012;Lo´pez and Gonza´lez, 2013), highlighting Xenopus as a valid model for the present anatomical study.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…The specificity of the antibodies had previously been tested in most of the species used in this comparative analysis (Ferran et al, 2009; Moreno et al, 2010; Morona et al, 2011; Domínguez et al, 2013, 2014; Joven et al, 2013a,b). Moreover, the immunoblotting conducted with brain extracts of all the species used showed that the Pax6 and Pax7 antibodies labeled a single band at comparable molecular weight across species ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The mouse anti-Pax6 and anti-Pax7 antibodies developed by Kawakami et al (1997) are the most widely used in anatomical studies, independently of the species studied (Ferran et al, 2008, 2009; Morona et al, 2011; Moreno et al, 2012b; Bandín et al, 2013, 2014; Domínguez et al, 2013, 2014; Joven et al, 2013a,b). In order to develop the antibodies against Pax6 and Pax7, Kawakami et al (1997) first determined the complete nucleotide sequence of the full-length cDNA encoding for Pax6 and Pax7.…”
Section: Methodsmentioning
confidence: 99%